Misi Penginjilan Yesus (MATIUS 9:35-38) dan Implementasinya bagi Mahasiswa Prodi Teologi IAKN Tarutung - Mega Intan Tambunan; Herdiana Boru Hombing; Enda Dwi; Megawati Manullang; Bernhardt Siburian (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to determine Jesus' evangelistic mission based on Matthew 9:35–38 and its implementation for students of the Theology Study Program of IAKN Tarutung. The research method in writing this scientific paper is a combination of qualitative and quantitative methods. For the qualitative method using a library research approach while the quantitative method with 10 informants of the Theology Study Program of IAKN Tarutung. In this study will be explored the mission of Jesus' evangelism based on Matthew 9:35–38 and its implementation for students of the Theology Study Program of IAKN Tarutung. The results of the study of the exegesis of Matthew 9:35–38 Jesus' evangelistic mission is to travel, teach, preach the Gospel, heal the sick, Jesus' compassion. From this study also shows that students have understood the essence of Jesus' evangelistic mission theologically. This is influenced by the learning of the Contemporary Missiology course which reveals the basic principles of the mission based on the Gospel of Matthew. However, implementation in the field is still very limited. As many as 70% of the data obtained in this study indicate that students have not yet pursued mission as a calling, but rather as an academic task. Challenges faced in carrying out mission for students of the Theology Study Program at IAKN Tarutung include a lack of self-confidence, an inapplicable curriculum, and low spiritual awareness. This study emphasizes that theological understanding needs to be supported by a curriculum system, spiritual formation, and a contextual service community so that students are able to live out the mission of evangelism comprehensively as exemplified by Jesus Christ.